TINGKAT KEMATANGAN GONAD DAN INDEKS KEMATANGAN GONAD KERANG POKEA (Batissa violacea var. celebensis, von Martens 1897) DI SUNGAI LAEYA KONAWE SELATAN - Dian Resky Pratiwi; Bahtiar Bahtiar; Muslim Tadjuddah; Sadri Sadri (Universitas Mataram, 2019)
Abstract : Pokea clam is one of the resources utilized, but its existence continues to experience a decrease in quality and quantity. This study aims to analyze the Gonad Maturity Level (TKG), Gonad Maturity Index (IKG) of pokea clam. Research begins in September 2016 - February 2017 on the Laeya River. The sampling method used is the swept area with the